IMPROVING MATHEMATICS LEARNING OUTCOMES THROUGH THE TEAM GAMES TOURNAMENT MODEL USING “GURITA SOAL” LEARNING MEDIA - Elyasarikh , Annisa Alvi; Prasetya, Slamet Puji; Lestari, Tri (Magister Scientiae, 2026)
The mathematics learning outcomes of students in Grade IX-E at one of the state junior high schools in Surabaya were below the teacher’s expectations. Therefore, the Team Games Tournament (TGT), a cooperative learning model, was implemented using the “Gurita Soal” learning media to improve students’ learning outcomes. This study aimed to examine the implementation of TGT using the “Gurita Soal” learning media, which combines cooperative competition and interactive learning tools to simultaneously enhance cognitive outcomes and classroom engagement.  This study employed a Classroom Action Research (CAR) design consisting of two iterative cycles, each including planning, implementation, observation, and reflection stages. Data were collected through cognitive tests and observation sheets and analyzed using descriptive statistics and qualitative analysis. The results showed that the average student learning outcomes increased from 78.26 in the pre-action stage to 88.53 in Cycle I and 92.24 in Cycle II. In addition, improvements were observed in student participation and teacher instructional practices during the learning process.  It can be concluded that this approach effectively improves students’ mathematics learning outcomes. Future research is recommended to integrate more adaptive digital learning media to support diverse student characteristics